Implementation of Administrative Law Principles in Public Service Delivery at the Buol Regency Library and Archives Service - Alhamid Baharuddin; Ahmad S. Morad (Journal of Innovative and Creativity, 2025)
Public services at the Buol Regency Library and Archives Service (DPAD) play a crucial role in supporting the provision of information, public literacy, and the management of government archives. However, based on existing conditions, various issues remain, such as inconsistencies between service procedures and administrative law provisions, a lack of technical regulations that serve as the basis for service operations, and suboptimal transparency in providing information to the public. Limited human resources and digital infrastructure also slow down the service process, impacting the quality of service provided. This study aims to analyze the implementation of administrative law principles in the provision of public services at the Buol Regency DPAD. The approach used is a juridical-empirical approach with qualitative descriptive methods. Data were obtained through in-depth interviews, field observations, and documentation reviews with officials, employees, and service users. The results indicate that the application of the principle of legality is evident in policy formulation, but has not been fully implemented in technical service delivery because some procedures lack a sufficient written legal basis. The principle of accountability is implemented through performance reports and internal audits, but has not yet led to outcome-based measurement. The principle of transparency has also been implemented through public information disclosure, but this remains limited to the provision of formal information and is not yet fully accessible to the public. Inhibiting factors include limited civil servant competence, inadequate digital infrastructure, and weak internal oversight. This study recommends the development of more comprehensive standard operating procedures (SOPs) based on the principle of legality, increasing the legal capacity of civil servants, and strengthening the digitalization of archives and services. Overall, this study confirms that strengthening the principles of administrative law is key to realizing good governance in Buol Regency.